Transforming growth factor β (TGF-β) expression in isolated and cultured rat hepatocytes - Gao, Chunfang; Gressner, G.; Zoremba, M.; Gressner, A. M. (Journal of cellular physiology, 1996)
It is still a subject of debate whether hepatocytes have the ability to express TGF‐β. Therefore, we investigated in freshly isolated and in monolayer cultures of rat hepatocytes the expression of TGF‐β isoforms at the RNA and protein level applying RT‐PCR, immunocytochemistry, immunoblotting, and functional assays of TGF‐β, TGF‐β1, ‐β2, and ‐β3 transcripts were detected in cultured cells, and the level of mRNA increased up to 48/72 h, but TGF‐β1 transcripts were absent in freshly isolated cells. Using APAAP stainings the proteins of all three TGF‐β isoforms were observed in hepatocyte cultures from 5–96 h, but in hepatocytes in the liver in situ and in freshly isolated cell suspensions TGF‐β staining was negative. SDS‐PAGE under reducing conditions followed by Western blotting detected in cell lysates the subunit of mature TGF‐β at about 13 kd. Analysis of TGF‐β bioactivity with the mink cell (Mv1Lu) proliferation inhibition assay and competitive radioligand assay confirmed in activated (i.e., acidified and subsequently neutralized) hepatocyte‐conditioned media the presence of TGF‐β, which, however, is almost entirely in the latent form. It is concluded that TGF‐β can be expressed in cultured hepatocytes and that the level of expression is quickly upregulated under abnormal, not yet known, microenvironmental conditions. © 1996 Wiley‐Liss, Inc.